Rate constants for the slow Mu + propane abstraction reaction at 300 K by diamagnetic RF resonance. Issue 30 (14th August 2015) - Fleming, Donald G.; Cottrell, Stephen P.; McKenzie, Iain; Ghandi, Khashayar
<x xml:space="preserve">Abstract</x> The rate constant for the slow Mu + propane abstraction reaction has been determined by diamagnetic RF resonance. The curves show simulations of the μSR resonance signal. This study provides an important new test of reaction rate theory for the alkanes.